RP-HPLC method development and validation for simultaneous estimation of Cilnidipine, Atenolol and Chlorthalidone - Solanki, Vishal Singh; BISHNOI, RAM SINGH; Baghel, Raviraj; Jain, Deepti (Journal of Drug Delivery and Therapeutics, 2018)
A simple precise and economical reverse phase high performance liquid chromatographic method has been developed and validated for the simultaneous estimation of Cilnidipine (CDP), Atenolol (ATL) and Chlorthalidone (CTD).The chromatographic separation was achieved by using Hypersil- keystone C18 (4.6 x 250mm, 5μm) under isocratic conditions The mobile phase consisted of methanol and triple distilled water (80/20, v/v) having pH 7 with a flow rate of 1.0 mL/min. The eluents were monitored at 225 nm for simultaneous measurement.The selected chromatographic conditions were found to effectively separate CDP (Rt: 3.25 min), ATL (Rt: 5.366 min) and CTD (Rt: 9.025 min) having good resolution. The developed method was validated for linearity, accuracy, precision, LOD, LOQ, robustness and for system suitability parameters as per ICH guidelines. In this study, an excellent linearity was obtained with r2 = 0.999, r² = 0.999, r² = 1, for CDP, ATL and CTD respectively. The developed chromatographic method proved to be simple, precise, accurate, robust and reproducible Thus, this method would be employed for routine simultaneous quantification of CDP, ATL and CTD in bulk form or tablet dosage form. Keywords: Cilnidipine, Atenolol and Chlorthalidone, RP-HPLC.